Bilan du programme autrichien de recherche sur les paysages - Karolina Begusch-Pfefferkorn (Revue de Géographie Alpine)
Austrian Landscape Research, a programme of the Austrian Ministry of Science, has created scientific foundations for the sustainable development of Austrian landscapes and regions (plus bordering regions). Landscapes and regions were to be explored from different angles; implementing the research findings was to be part of the research work. The programme was designed to make room for science open to society, for unconventional ideas, methods, and courses of action. Programmatic targets and research principles supported this intent. The results of the programme met with national and international approval. The ALR knowledge balance is an attempt at presenting and assessing the achievements of this comprehensive contract research programme.